Serum interleukin-6 and associated nociceptive parameters following subcutaneous infiltration of lidocaine alone, tramadol alone, and their combination in red Sokoto goat undergoing rumenotomy - Abubakar, Nura; Buhari, Salisu; Yakubu, Abubakar Sadiq; Abubakar, Adamu Abdul; Ismaila, Mohammad Sani; Bodinga, Hassan Abubakar; Dahiru, Ashiru; Ahmad, Umar Salisu; Zaid, Shehu (Edelweiss Applied Science and Technology, 2025)
The clinical practice of combining one or more drugs is gaining attention for enhancing efficacy, leading to quicker onset of action, longer duration of effect and minimising side effects. Previous studies showed that combining lignocaine and tramadol in an epidural injection significantly extended the duration of analgesia produced when compared to the use of lignocaine alone. The significance of this study is aiming toward improved pain management during surgery, especially in goats. In this study, the analgesic effects of subcutaneously administered lignocaine alone (7 mgkg-1), tramadol alone (3 mgkg-1), and their respective combination of 3.5 and 15 mgkg-1 on pain in goats undergoing rumenotomy were compared. The experiment was carried out on fifteen healthy (N=15) Red Sokoto goats. Blood was drawn from the jugular vein at seven distinct time intervals during the course of the experiment (0, 1, 2, 3, 4, 5, 6 and 7 hours) and serum was extracted. The severity of pain was ascertained by measuring serum level of IL-6 and the nociceptive response to a pain stimulus using a clinical algometer. This study revealed that the combination of lidocaine (03.78 minutes) and tramadol (3.68 minutes) has a quicker onset of action (2.01±0.42 minutes) and a more extended duration of activity (79.5 minutes) when compared to lidocaine (60 minutes) and tramadol (55.75 minutes) administered separately. There was no significant difference (P>0.05) in serum IL-6 before and after the administration of lidocaine, tramadol, or their combination. This study has demonstrated that the lidocaine-tramadol combination at respective doses of 3.5 and 1.5 mgkg-1 has a quicker onset and longer duration of activity when subcutaneously administered at the surgical site, in comparison with lidocaine alone and tramadol alone at respective doses of 7 and 3 mgkg-1. However, there was no remarkable difference in the serum pain biomarker (IL-6) among the three different treatments. Subcutaneous infiltration of the combination of lidocaine at 3.5 mgkg-1 with tramadol at 1.5 mgkg-1 via the inverted L block technique can be employed as an alternative to conventional lidocaine alone to achieve loco-regional analgesia for a more prolonged duration in goats to conduct laparotomy. Clinically, this drug combination could be useful in surgeries requiring extended regional anaesthesia, reducing the need for repeated dosing, hence improving animal welfare.